Relationship between the meal frequency and timing with overweight and obesity in trujillan adults.: Relación entre la frecuencia y horario de alimentación con el sobrepeso y obesidad en adultos trujillanos - Lam Cabanillas, Eduardo R. (2022)
Introduction: Overweight and obesity are rapidly growing in the world, with a higher risk of chronic diseases. Nutritional strategies are of great interest for weight loss and control, such as the influence of meal frequency and timing. Objective: To determine the relationship between the meal frequency and timing with overweight and obesity in the adult population of Trujillo between 30 and 70 years old. Methods: Descriptive, cross-sectional study with a quantitative approach. A sample of 160 participants, between 30 and 70 years old, is included; the data was collected through a virtual survey. Participants were classified into a normal weight group established by a BMI between 18.5-24.9 and an overweight-obese group established by a BMI greater than or equal to 25. An expert-validated questionnaire was produced to assess the meal frequency and timing. Results: Of the 160 participants, 61.88% were female, 40% were between 30-39 years old. The normal weight group was made up of 60 participants; and overweight-obesity, per 100 participants. In the statistical analysis, a significant difference was evidenced between the level of low-moderate physical activity (p = 0.019), the meal frequency did not present a significant difference (p = 0.477) and within the meal timing, the consumption of subsequent dinner at 8:00 pm showed a significant difference (p = 0.021), as well as the consumption of intermediates after 5:00 pm (p = 0.016), Conclusion: Consuming food during the night in a time after 8:00 pm is significantly associated with the risk of overweight and obesity; while in the meal frequency it does not appear.